The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1021/ic060827f
|View full text |Cite
|
Sign up to set email alerts
|

Necklace-like Hollow Carbon Nanospheres from the Pentagon-Including Reactants:  Synthesis and Electrochemical Properties

Abstract: Necklace-like hollow carbon nanospheres (CNSs) have been successfully synthesized from the pentagon-including reactants, which provide an auxiliary example for the theoretical prediction that necklace-like hollow CNSs are assumed to be composed of the regular occurrence of nonhexagonal rings at the atomic level. Benefits of the as-obtained hollow CNSs also arise from the high Brunauer-Emmett-Teller value of 594.32 m(2)/g and a narrow pore distribution at 5 nm. The electrochemical hydrogen storage experiments f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 34 publications
3
33
0
Order By: Relevance
“…Probably, the most relevant re-60 search in this area has been done by Beguin, Frackowiak 61 and co-workers [13][14][15][16][17][18][19]. Similar results have been obtained 62 by other authors using ordered porous carbons with tailored 63 pore size [12], carbon blacks [20] or necklace-like hollow car-64 bon nanospheres [21]. From these studies, the role of porosity 65 has been discussed as well as the importance of the dangling 66 carbon atoms in the hydrogen storage.…”
mentioning
confidence: 61%
“…Probably, the most relevant re-60 search in this area has been done by Beguin, Frackowiak 61 and co-workers [13][14][15][16][17][18][19]. Similar results have been obtained 62 by other authors using ordered porous carbons with tailored 63 pore size [12], carbon blacks [20] or necklace-like hollow car-64 bon nanospheres [21]. From these studies, the role of porosity 65 has been discussed as well as the importance of the dangling 66 carbon atoms in the hydrogen storage.…”
mentioning
confidence: 61%
“…Many reactions have also been performed with chlorinated carbon reactants, e.g. C 2 Cl 4 [90] and the products obtained have included hollow carbon nanospheres [91]. Lv et al have reported on the effect of using chlorine-containing precursors to synthesize micrometer-long continuous FeNi nanowires inside thin-walled CNTs [92].…”
Section: Halidesmentioning
confidence: 99%
“…Here, the 3D CNNWs obtained by the reaction of ferrocene with CCl 4 , C 2 Cl 4 , and C 4 Cl 6 showed high surface areas of 564, 680, and 552 m 2 /g, respectively, which were all higher than those of other carbon nanostructures in the previous reports [16,17] .…”
Section: Surface Area Studies Of Cnnwsmentioning
confidence: 49%